Implementasi Wireguard Sebagai Koneksi Menggunakan Routing Mikrotik - Muhammad Ilham Ikhwandi; Azmuri Wahyu Azinar; Sumarno (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
The integration of WireGuard and RouterOs mikrotik allows mikrotik users to easily create a secure and fast virtual private network using Virtual Private Network (VPN) for international networks that can provide many benefits, including security, privacy, unlimited access, and more efficient network management. The government has the right to monitor and take action if there is an indication of VPN misuse for illegal activities. WireGuard uses a combination of modern cryptography and network techniques to achieve high performance and strong security. In this study, researchers used the SDLC (Software / System Development life cycle) method where the method is quite detailed covering six stages, namely: planning (Planning), analysis (analysis), design (design), implementation (implementation), testing (testing), maintenance (maintenance). At the testing stage, there needs to be control and monitoring of the local network and packet los that will see changes in the IP address of the user, the aim is to maintain stability when using a Virtual Private Network (VPN).